Reliability Evaluation of Wireless Sensor Networks Using Logistic Regression - Fei Huang; Zhipeng Jiang; Sanguo Zhang; Suixiang Gao (2010 International Conference on Communications and Mobile Computing, 2010)
One essential requirement for WSN is the reliability of the applications. Performance evaluation, therefore, is of great significance before the successful deployment of the network. In this paper, we consider the reliability based on a specific type of network lifetime. Our network lifetime is defined based on the representative consideration of coverage and connectivity and has a common application background. After simulating the network lifetime, we divide the network into ''reliable" and ''not reliable" and use the logistic regression model to evaluate the network reliability based on the simulation data. We also address the bias reduction model to solve the linearly separable problem. Logistic regression is widely used in epidemiologic, credit assessment of finance and so on. So far as we know, this is the first time that logistic model is used in the performance evaluation for wireless sensor networks. The main contribution of this paper is to use logistic regression method for the first time to evaluate WSN reliability other than the model itself. We also show the extended applications of logistic regression model in evaluating other parameters in WSN.